Patterns and implications of spatial covariation in herbivore functions on resilience of coral reefs - Dana T. Cook; Sally J. Holbrook; Russell J. Schmitt (Scientific Reports)
Abstract Persistent shifts to undesired ecological states, such as shifts from coral to macroalgae, are becoming more common. This highlights the need to understand processes that can help restore affected ecosystems. Herbivory on coral reefs is widely recognized as a key interaction that can keep macroalgae from outcompeting coral. Most attention has been on the role ‘grazing’ herbivores play in preventing the establishment of macroalgae, while less research has focused on the role of ‘browsers’ in extirpating macroalgae. Here we explored patterns, environmental correlates and state shift consequences of spatial co-variation in grazing and browsing functions of herbivorous fishes. Grazing and browsing rates were not highly correlated across 20 lagoon sites in Moorea, French Polynesia, but did cluster into 3 (of 4) combinations of high and low consumption rates (no site had low grazing but high browsing). Consumption rates were not correlated with grazer or browser fish biomass, but both were predicted by specific environmental variables. Experiments revealed that reversibility of a macroalgal state shift was strongly related to spatial variation in browsing intensity. Our findings provide insights and simple diagnostic tools regarding heterogeneity in top-down forcing that influences the vulnerability to and reversibility of shifts to macroalgae on coral reefs.